DEVELOPMENT OF CORPORATE SOCIAL RESPONSIBILITY UNDER AGGRAVATION OF THE CONTEMPORARY GLOBAL ISSUES - N. Grazhevska; A. Mostepaniuk (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article deals with the role and importance of corporate social responsibility as an important mechanism for overcoming the crisis of the welfare state and to mitigate the social problems caused by the world globalization processes. The experience of post-socialist countries, the Baltic States and Ukraine in this field is analyzed and barriers to effective implementation of CSR in the national economy are identified. The priority of the state policy to promote socially responsible business behavior in Ukraine is proved.